Haemodynamic Changes During Laparoscopic Cholecystectomy Under Sevoflurane Anaesthesia (Journal of Fatima Jinnah Medical University, 2018)
Aims & Objectives: The objective of the study is to determine the effect of sevoflurane on the haemodynamic changes during laparoscopic cholecystectomy. Methods: In this study total 160 cases were selected. Induction of anaesthesia was done with Thiopentone Na and intubation, with cuffed endotracheal tube, using succinylcholine I/V. Anaesthesia was maintained with Nitrous oxide (66%) in Oxygen and Sevoflurane at 1 MAC. Changes in heart rate and blood pressure were noted during surgery. Conclusion: Sevoflurane provided good operating conditions throughout the procedure. It provides a safe and effective intraoperative control of cardiovascular homeostasis.
Keywords: Cholecystectomy, Laparoscopic, Haemodynamics, Sevoflurane